Enhancing palm oil inventory control support analytic tools - Fatkhurrahman, Manani; Siti Zubaidah, Ismail (Penerbit UMP, 2021)
Product-Service System (PSS) inventory control in Malaysian palm oil industry is a blend of product or services that offer a good worth in regards to economics and also environment. This paper intends to establish a support analytic device for implementation in the palm oil industry. Many smallholder businesses do not have any kind of supply systematic record-keeping to keep the supply in a respectable operating. The existing technique of figuring out supply takes a yearly physical inventory by comparing the real inventory with document levels. This method is a pricey as well as lengthy effort. In this paper, an inventory control web-based application device was developed to meet customer demand and methodical record management is significant to have respectable tracking and also analysis as part of being effective. This tool will certainly help the firm to save the main stock data-based on collected information and also to monitor the motion of the stocks to ensure that whatever is controlled as well as in great order. This tracking process makes it much easier for firms to decide and also for forecasting for products and services in palm oil plantation.